2005
DOI: 10.1177/1073191104271483
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Schedule of Compulsions, Obsessions, and Pathological Impulses (SCOPI)

Abstract: This article describes a factor analytically derived, self-report instrument-the Schedule of Compulsions, Obsessions, and Pathological Impulses (SCOPI)-using data from college students, adults, psychiatric outpatients, and patients with obsessive-compulsive disorder (OCD). The five SCOPI scales all are internally consistent (with coefficient alphas of .80 and higher) and are strongly stable across a 2-month interval (with retest correlations ranging from .79 to .82). They also show good convergent and adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 38 publications
2
102
0
Order By: Relevance
“…The latter factors are supported by item-level analyses (Summerfeldt et al, 1997;Denys et al, 2004), and Taboo Thoughts is consistent with the "pure obsessions" factor reported in two category-level analyses (Baer, 1994;Hantouche and Lancrenon, 1996). Beyond the YBOCS-SC, the proposed model corresponds to five-factor solutions derived from two self-report measures of OCD symptoms, the 42-item ObsessiveCompulsive Inventory (Wu andWatson, 2003) and the Schedule of Compulsions, Obsessions, and Pathological Impulses (Watson and Wu, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The latter factors are supported by item-level analyses (Summerfeldt et al, 1997;Denys et al, 2004), and Taboo Thoughts is consistent with the "pure obsessions" factor reported in two category-level analyses (Baer, 1994;Hantouche and Lancrenon, 1996). Beyond the YBOCS-SC, the proposed model corresponds to five-factor solutions derived from two self-report measures of OCD symptoms, the 42-item ObsessiveCompulsive Inventory (Wu andWatson, 2003) and the Schedule of Compulsions, Obsessions, and Pathological Impulses (Watson and Wu, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several self-report instruments aiming at a comprehensive measurement of the heterogeneous clinical picture have been developed, e.g., the Padua Inventory (Sanavio, 1988) and its revisions (Burns, Keortge, Formea, & Sternberger, 1996;van Oppen, Hoekstra, & Emmelkamp, 1995), the Vancouver Obsessional Compulsive Inventory (Thordarson et al, 2004), the Schedule of Compulsions, Obsessions, and Pathological Impulses (Watson & Wu, 2005), and the OCI-R (Foa et al, 2002). Most of these instruments have been translated into various languages and validated in other cultural contexts.…”
mentioning
confidence: 99%
“…The IMAGE-HD protocol included two neuropsychiatric scales (described in : 1) the Frontal Systems Behavior Scale (FrSBe) (Grace et al, 2001), which measures neuropsychiatric symptoms of fronto-striatal dysfunction; and 2) the Schedule of Obsessions, Compulsions and Pathological Impulses, SCOPI (Watson and Wu, 2005), which provides an assessment of these Structural and functional MR images were acquired at 3T (Siemens Magnetom Tim Trio) over the three testing visits. Data acquisition, pre-processing, and quality control procedures were consistent across time points.…”
Section: Neuropsychiatric Assessmentsmentioning
confidence: 99%